Two new deep-sea anglerfishes (Oneirodidae and Gigantactidae) from Taiwan, with synopsis of Taiwanese ceratioids - Ho, Hsuan-Ching; Shao, Kwang-Tsao (Zootaxa, 2019)
Two new species of deep-sea anglerfishes are described on the basis of specimens collected from off northeastern Taiwan. Oneirodes formosanus sp. nov., based on one adult female, differs from its congeners in having a deep caudal peduncle (15.4% SL) and esca with a single simple, elongate, unbranched, internally pigmented, anterior escal appendage; a simple, elongate, posterior escal appendage; an elongate terminal escal papilla; and no medial and lateral escal appendages. Gigantactis cheni sp. nov., based on three adult females, differs from its congeners in having a series of unpigmented filaments at base of illicium; a black terminal elongated esca bearing numerous dermal spinules; relatively more jaws teeth with the outtermost ones relatively short. A synopsis of Taiwanese species of the suborder Ceratioidei is provided.